Measurement of Normal Portal Vein Diameter by Ultrasound - Jha, Akhilesh Kumar; Shah, Shashi Shekhar Prasad; Sah, Dambar; Akthar, MD Kalim; Mahato, Rajan Kumar; Rimal, Bikranta; Chaurasiya, Chandan; Jha, Rakesh Kumar; Thakur, Amit Kumar; Adhikari, Trayush (Med Phoenix, 2023)
Introduction: Measurement of the diameter of the portal vein may be particularly important in detecting and evaluating patients with portal hypertension as well as some other clinical disorders.This study is aimed at determining the mean portal vein diameter based on age, gender and anthropometric variables. Materials and Methods: A cross-sectional study was performed on a total of 195 apparently healthy individuals with overnight fasting and normal ultrasonographic findings of the liver. Portal vein diameter was measured and correlated with age, height, weight and BMI of the participants. Results: The mean portal vein diameter was 9.57 ± 0.66mm for both sexes. The mean value for males was 9.71 ± 0.67mm, and 9.46±0.64mm among females. There was a positive correlation between the PV diameter and age, height, weight and body mass index (P≤ 0.05). Conclusion: The measurement of the portal vein diameter using sonography is an important cornerstone for diagnosing patients with portal hypertension and also has a reasonable degree of accuracy.